PENGGUNAAN MEDIA WAYANG PADA PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN HASIL BELAJAR DI SEKOLAH DASAR - Sumaryanti, Eka; Sabri, Tahmid; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the students?s learning outcomes in thematic learning using wayang as the learning media. The method of this research is classroom action research. The subject of this research is first grade students of SD Negeri 17 Pereges. This research is done in three cycle where in each cycle has one phase: preparation, implementation, observation, and reflection. Technique of data collecting is observation and evaluation. The tool of data collecting in this research is IPKG I observation sheet, IPKG II observation sheet, and evaluation question in form of 10 multiple choice, 5 essays, and 1 question required skill to be shown. Technique of analysis data is qualitative and quantitative. Based on the data analysis, teacher ability on planning and implementing is improved. In the first cycle, the score of teacher ability on planning is 2.98 point, the second cycle is 3.64 point, and the third cycle is 4. Meanwhile, on the teacher implementation, the score in the first cycle is 3.39, the ceond cycle is 3.78, and the third cycle is 3.96. The result of students? evaluation is 56.25% in the first cycle, 75% in the second cycle, and 100% in the third cycle. Keywords: Wayang, Thematic Learning, Learning Outcomes,